THE ENIGMATIC GUIDE AND THE FORMING OF THE SOUL: A COMPARATIVE-TYPOLOGICAL STUDY OF FAIRY-TALE ARCHETYPES IN LUQMON BO’RIXON’S “SIRLI MUALLIM” AND PATRICK NESS’S “A MONSTER CALLS” - Yo’ldosheva Go’zal Nasrullayevna (International Journal of Literature and Language Studies, 2026)
This article offers a comparative-typological reading of two works of modern children’s and young-adult prose – the Uzbek writer Luqmon Bo’rixon’s novella Sirli muallim (“The Mysterious Teacher,” 1991; collected 2006) and the English-language writer Patrick Ness’s A Monster Calls (2011) – in order to show how inherited fairy-tale archetypes are reactivated in contemporary literature as instruments of spiritual and moral formation. Drawing on the morphological tradition of Vladimir Propp, the archetypal psychology of Carl Gustav Jung, Joseph Campbell’s account of the mentor and the “supernatural aid,” and Bruno Bettelheim’s psychology of the fairy tale, the study argues that both texts are organised around a single deep structure: the arrival of an enigmatic guide who subjects a younger protagonist – or a whole community of learners – to a symbolic trial and thereby precipitates an inner awakening. The analysis identifies the convergent core of this structure (the wise or supernatural mentor, the motif of the test, and the function of story as a healing and educative force) while foregrounding the national-cultural specifics that distinguish Bo’rixon’s Eastern, classroom-centred ethical didacticism from Ness’s Western, grief-centred therapeutic individualism. The article concludes that comparative archetypal reading is a productive framework for understanding how children’s literature across traditions performs the shared work of spiritual education.